Particle Swarm Optimization for Parameter Tuning in Machine Learning Algorithms - H. Qadir , Rukhsar; A. Ali , Nzar (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Heart disease is one of the leading causes of death. One area where machine learning can be used is in the prediction of heart disease. In the medical area, classification is one of the Machine Learning techniques employed because of its high accuracy. The utilization of features and dimensions in the dataset affects the accuracy of the classification algorithm. In this paper using the PSO algorithm, we present an optimization strategy for tuning support vector machine (SVM) parameter values to classify a dataset of heart disease. The test results show that the classification using SVM with PSO can improve accuracy better than the classification using SVM without PSO, namely the determination of the parameters randomly. Results show that heart disease data classification without PSO accuracy is 0.7711 in time heart disease dataset classification with PSO accuracy increased to 0.8159 after optimizing the main two parameters of SVM C and gamma.